Avaliação do uso de inversor de frequência em estação elevatória de água - Cherem, Lucas Braga (Universidade Federal do Tocantins, 2017)
Electricity is primordial for basic sanitation development, and this sector was responsible for 2.4% of Brazilian energy consumption in 2015. In our recent scenario, seeking for more energetic efficient processes is mandatory for reducing the environmental impact as well as costs incurred from a lower energy consumption for companies responsible for public sanitation. The objective of this current study was the evaluation of energetic efficiency technique for pumping systems. A Variable Frequency Drive was installed to vary the engine rotation aiming to reduce the flow rate when compared to the standard usage of a flow control valve. The analysis was made on a system of water supply in the municipality of Palmas-TO where a 100hp motor was ignited by a soft starter. This study monitored the following parameters: power, flow rate, pressure, pumped water volume and system energy consumption; this allowed proving the efficiency of the usage of the variable frequency drive which increased the system yield as well as reduced energy consumption in approximately 22%. It was then concluded that on systems where there are flow rate restrictions by valves it is economically feasible to install a variable frequency drive and the payback for the initial investment will come in power savings, to the case in question the payback is 10 months.